Image_9.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
Once the dough is kneaded, it is divided into small, round portions. Each portion will be used to make an individual bhakri. Next, the dough is shaped into flat discs by turning it in a circular motion. Simultaneously, Urmila removes excess dough by pressing down on it with the palms of her hands.